2016
DOI: 10.1103/physreva.94.032334
|View full text |Cite
|
Sign up to set email alerts
|

Stationary states in quantum walk search

Abstract: When classically searching a database, having additional correct answers makes the search easier. For a discrete-time quantum walk searching a graph for a marked vertex, however, additional marked vertices can make the search harder by causing the system to approximately begin in a stationary state, so the system fails to evolve. In this paper, we completely characterize the stationary states, or 1-eigenvectors, of the quantum walk search operator for general graphs and configurations of marked vertices by dec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Let G = (V, E) be an undirected graph and M be a connected set of marked vertices. In [1] the authors showed Theorem 1. If M is bipartite, then we can assign amplitudes to neutralise the shortages at each marked vertex if and only if the sums of the shortages on both partite sets are equal.…”
Section: Corrections 1theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…Let G = (V, E) be an undirected graph and M be a connected set of marked vertices. In [1] the authors showed Theorem 1. If M is bipartite, then we can assign amplitudes to neutralise the shortages at each marked vertex if and only if the sums of the shortages on both partite sets are equal.…”
Section: Corrections 1theoremmentioning
confidence: 99%
“…Note that authors have considered only stationary states with the amplitudes u → v for arbitrary unmarked u and arbitrary v being all equal. Since according to Theorem 2 from [1] only these amplitudes has impact on overlap between stationary state and initial state, a can be upper-bounded by ā of the form…”
Section: Corrections 1theoremmentioning
confidence: 99%
“…Search using SKW's scheme has been explored on a large number of graphs, including the hypercube [1], two-and higher-dimensional grids [25,35,36], Sierpinski gaskets [37], complete graphs with and without self-loops [38], and the simplex of complete graphs with a fully marked clique [26]. Other explorations include the impact of internal-state measurements [39] and stationary states [40]. Now we prove that Szegedy's quantum walk with absorbing vertices is equivalent to SKW's coined quantum walk search scheme.…”
Section: Search With Absorbing Verticesmentioning
confidence: 99%
“…It first appeared in [25], where this search scheme on the complete graph with a self-loop at each vertex is exactly equivalent to Grover's algorithm (apart from a factor of 2). Other investigations of this quantum walk search operator SCQ include the complete graph with an arbitrary number of self-loops per vertex [38], search with potential barriers [32], improving the success probability by measuring the coin state [39], and the effect of stationary states [40]. All of these results directly map to Santos's walk W q1 .…”
Section: Search With Grover's Oraclementioning
confidence: 99%
“…For example, consider the discrete-time coined quantum walk that was first proposed by Meyer in the context of quantum cellular automata [6,7] and later recast as a quantum walk by Aharonov et al [8]. Its ability to search the 2D grid has been explored for several arrangements of marked vertices [9,10,11,12,13,14], and one problematic configuration is when the marked vertices lie along a diagonal, such as in Fig. 1b.…”
Section: Introductionmentioning
confidence: 99%